(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Hemorrhoids are very common anorectal diseases that affected any age groups and both genders. There are different and several options for treatment of patients with hemorrhoids .ranging from conservative approach with dietary modifications ,rubber band ligation, sclerotherapy injection, diathermy coagulation, or minimal invasive procedures like; open surgical procedure and recently various types of laser was introduced such as carbon dioxide (CO2) laser, and the neodymium :yttrium – aluminum – garnet (Nd: YAG ) laser procedures. In our study, we choose (1000 patients) all of them were free of medical diseases, those lie into two main groups , 500 patients (males and females) with different age groups were treated with conventional open surgical (Milligan – Morgan) hemorrhoidectomy operation ,and 500 patients (males and females) with different age groups were treated with minimally invasive diode laser hemorrhoidoplasty technique . Laser hemorrhoidoplasty technique is used to treat the patients with 2nd and 3rd degree hemorrhoids, as an outpatients procedure without causing any additional harm or injuries to the surrounding normal (healthy) tissues, and significantly less post-operative complications with very short operative time and very rapid return to the normal daily activities.